Metformin suppresses self‐renewal and stemness of cancer stem cell models derived from pluripotent stem cells. (15th July 2021) - Zahra, Maram H.; Afify, Said M.; Hassan, Ghmkin; Nawara, Hend M.; Kumon, Kazuki; Seno, Akimasa; Seno, Masaharu
Abstract : Metformin exhibits anti‐cancer activities in various types of tumours while it is prescribed as the first‐line drug for type 2 diabetes. Since new evidence has recently suggested that metformin could target cancer stem cells (CSCs) and prevent their recurrence, repositioning of metformin could be considered as a candidate for anti‐CSC agent. In this study, we assessed the effect of metformin on the cancer stem cells developed from induced pluripotent stem cells. As the result, metformin significantly suppressed the self‐renewal ability of CSCs when assessed by 3‐(4, 5‐dimethythiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay and cell counting methods exhibiting the IC50 as approximately 20 mM, which suppressed tube formation by CSCs on Matrigel reducing the angiogenic potential of CSCs. Cell cycle analysis showed that metformin reduced the percentage of cells in the S phase increasing the percentage of cells in G0/G1 phase. Moreover, the tumorigenicity of CSCs was found to be attenuated when the cells were injected with metformin. From these results, we concluded that metformin could be promising for targeted therapy by repositioning the widely available drugs with safety. Significance of the study: Metformin could target CSCs and prevent their recurrence, repositioning of metformin could be considered as a candidate for the anti‐CSC agent. In this paper, we assessed the effect of metformin on the CSCs developed from induced pluripotent stem cells. Here, we show that metformin suppresses the self‐renewal and tube formation abilities of CSCs. We also show that metformin reduces the percentage of cells in the S phase increasing the percentage of cells in G0/G1 phase. Moreover, the tumorigenicity of CSCs was found to be attenuated when grafted in vivo after treatment with metformin.